Pengaruh Independensi Komite Audit, Keahlian Akuntansi Dan Keuangan Komite Audit Terhadap Hubungan Opini Audit Going Concern Dengan Pergantian Auditor (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010- 2013) - Dwi Saputra, Erman; , Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2016)
This study aims to examine the relationship going concern audit opinion with a change of auditors, and to test the effect of audit committee independence and expertise of accounting and finance audit committee of its ties to the companies listed in the Indonesia Stock Exchange (BEI) 2010-2013. The sample in this study using manufacturing companies listed in Indonesia Stock Exchange in the year 2010-2013, with a population of 146 companies and a total sample of 25 companies, which were selected based on purposive sampling method possible with a 4-year period of observation and data analysis methods used are logistic regression. Based on this study can be a conclusion that the going concern audit opinion on the statistical effect change of auditor. While the independence of the audit committee, financial accounting expertise and audit committee does not affect the relationship going concern audit opinion by the auditor turnover.